Comparing numerical methods to estimate vertical jump height using a force platform - Chiu, L. Z. F.; Dæhlin, T. E. (Measurement in Physical Education and Exercise Science, 2020)
Males (n = 29) and females (n = 34) performed vertical jumps. Jump height was estimated from force platform data using five numerical methods and compared using intraclass correlation (p), and linear and rank regression standard error of estimate (SEE). Take-off velocity plus center of mass height at take-off and mechanical work methods were identical (p = 1.000) with small linear (SEE < 0.0001 cm) and rank order (SEE = 0) error. Integrating acceleration to displacement was nearly identical (p > 0.999), with small linear (SEE = 0.1 cm) and rank order (SEE < 1) errors compared to the above methods. Take-off velocity (p = 0.517) and flight time (p = 0.573) estimates were less than all other methods and had large linear (SEE = 2.1 cm) and rank order (SEE > 4) errors. Take-off velocity and flight time methods should be avoided due to systematic and random error.